Design of a test rig in support of e-clutch dynamics characterisation, modelling, and control. (7th September 2020) - Hoić, Matija; Hrgetić, Mario; Deur, Joško; Tissot, Andreas
E-clutch systems (also known as clutch-by-wire systems) have emerged recently as solutions that allow the powertrain control system to operate the clutch, while the driving procedures remain the same as with the regular manual transmissions (MTs). These systems offer possibilities of improved fuel economy and driving comfort over MT systems, while the driver maintains the existing driving habits. This paper presents the design of a test rig developed for a dry e-clutch equipped with a hydrostatic actuator mechanism driven by a spindle-based electric servomotor. The primary purpose of the test rig is to provide a basis for the experimental characterisation of both static and dynamic behaviours of the e-clutch, as well as to facilitate e-clutch model validation and control strategy verification. The use of the test rig is illustrated by presenting recordings of basic e-clutch static curves and time responses. These recordings are employed to validate axial dynamics and thermal dynamics models of an e-clutch, which are presented in the paper, as well.